Географічне поширення Betula humilis Schrank в Україні - Melnik, V.I.; Savchuk, L.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The map of Betula humilis Schrank distribution was formed as a result of the analysis of herbarium samples and literature data. The regressive changes in the area of the species are determined. Recommendations for protection of Betula humilis Schrank in Ukraine are proposed.